The fundamentals of the block starts & acceleration mechanics - Madiri, S. (IFAC, 2012)
Short powerpoint presentation of the author fat the International Festival of Athletics Coaching in Glasgow, 2012 about the fundamentals of the block starts & acceleration mechanics (biomechanics parameters, neuromechanics, neural & mechanical implications of a low block angle